L’art engagé : images de résistance, de résilience et de reconstruction humanitaire. - Dima Nachawi; Michela Villani (Genre, Sexualité et Société)
In this interview, Dima Nachawi discusses her commitment to the artistic work and demonstrates how the conflict and the obligation for her to leave the Syrian territory to go to Great Britain as a refugee brought about an artistic turning point. From that moment, it has become critical for her to tackle issues related to the political instability of her country, but also to her own condition as a refugee. Art has then become for her a visual support for "sending out messages" that she wanted to send to those who remained in the country. From then on, Dima has been using biographical elements to produce images of hope and promote an "aesthetic of reparation" (Best 2016). Dima Nachawi’s artistic writing is, at times, reminiscent of illustrative drawings for children, which she uses in humanitarian work, where she is engaged both as artist and as a social activist. For her, art is a support, images of resilience, constitute a visual aid to reconstruction.